Mathematical Literacy Challenges: Third-Grade Students’ Difficulties in Solving Multiplication Word Problems - Cut Farida Zuhra; Rora Rizki Wandini (Yayasan Sembilan Pemuda Indonesia, 2027)
This qualitative study analyzed the difficulties experienced by third-grade elementary school students in solving multiplication word problems and identified the stages at which those difficulties occurred. Eighteen students from SD Salsa, Indonesia, completed five multiplication word problems. Students whose written work showed difficulty were then examined through semi-structured interviews and document analysis. The evidence was organized according to five problem-solving stages: understanding the problem, identifying relevant information, selecting an operation, performing the calculation, and stating the final answer. Thirteen students (72.22%) completed the tasks without identified difficulty, whereas five students (27.78%) demonstrated recurring obstacles. Calculation and final-answer difficulties were the most frequent, affecting five students (27.78%) at each stage. Difficulties in understanding the problem, identifying key information, and selecting an appropriate operation each affected two students (11.11%). Two profiles emerged: conceptual difficulty, in which students could not interpret the problem or determine a strategy, and procedural difficulty, in which students selected multiplication correctly but could not calculate accurately. The findings show that success with word problems depends on the integration of mathematical language comprehension, conceptual understanding, and multiplication fluency. The study contributes a stage-based diagnostic framework that teachers can use to plan contextual practice, targeted scaffolding, and differentiated support in elementary mathematics classrooms.